2016
DOI: 10.1016/j.wneu.2016.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Cerebral Artery Aneurysms: Treatment and Outcome Analysis in 121 Patients

Abstract: Aneurysms of the PCA are infrequent and often associated with other vascular diseases. Microsurgery and endovascular treatment are effective for the occlusion of PCA aneurysms. The preservation or reconstruction of the parent vessel is crucial for favorable treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…3) There have been many reports on the treatment of PCA aneurysms, but the localization of aneurysms has been classified based on P1-P3, which is the main trunk, and it is unclear how many aneurysms that developed in the PCA temporal branch were included. 3,5) To our knowledge, there has been only one report on the treatment of aneurysms that developed in the PCA temporal branch, 6) and the present case that developed in the peripheral region may be rarer. Two classifications of the 4,7,8) The aneurysm in the present patient was located in the posterior temporal artery in the former classification and PITA in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…3) There have been many reports on the treatment of PCA aneurysms, but the localization of aneurysms has been classified based on P1-P3, which is the main trunk, and it is unclear how many aneurysms that developed in the PCA temporal branch were included. 3,5) To our knowledge, there has been only one report on the treatment of aneurysms that developed in the PCA temporal branch, 6) and the present case that developed in the peripheral region may be rarer. Two classifications of the 4,7,8) The aneurysm in the present patient was located in the posterior temporal artery in the former classification and PITA in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen patients who underwent treatment for aneurysms of fetal-type PCAs have been reported previously. Of these 18 patients, cerebral infarction occurred in 11 of the 15 patients who had undergone PAO without revasculari- zation, [1][2][3]5,[14][15][16][17] and symptoms were reported in 6 of the 11 cases (Table 1). The remaining 3 patients underwent internal trapping with OA-PCA bypass, which prevented cerebral infarction in 2 cases.…”
Section: Discussionmentioning
confidence: 99%
“…To our current knowledge, treating methods of AVMs are basing on 3 types [8][9][10][11][12], Arterial Embolization (AE), interventional management and surgical treatment. Previous studies have shown that the potential for the embolization treatment of recanalization of AVMs in other areas, then the follow-up visits confirmed the effective results [13,14].…”
Section: Discussionmentioning
confidence: 99%